Exploring potato seed research: a bibliometric approach towards sustainable food security - Lal, Priyanka; Tiwari, Rahul Kumar; Behera, Biswaranjan; Yadav, Malu Ram; Sharma, Eshita; Altaf, Muhammad Ahsan; Jena, Rupak; Ahmad, Ajaz; Dey, Abhijit; Kumar, Awadhesh; Singh, Brajesh; Lal, Milan Kumar; et al. (Frontiers in Sustainable Food Systems, 2023)
Potato is considered to be complete food that will not only ensure food security but also alleviate poverty. Seed production of potato requires specific temperatures and conditions. In response to the growing emphasis on sustainable production, there has been an increasing focus on research on tuber seed production. In our study, we have employed bibliometric analysis to investigate the trends in potato seed research and assess its correlation with sustainable development. Tabular analysis and network analysis are employed in the study to understand the prominent authors and institutions and research trends across time. For this purpose, Biblioshiny and Vosviewer software were used. The steps of bibliometric analysis were used, which included data retrieval from Dimensions software. Owing to its limitations, a major analysis was conducted without affecting the results. It was found from the analysis that it was SDG 2 that was mostly linked with the theme of potato seed production. The results depicted an increasing trend of publications and citations. Co-authorship analysis of authors showed high linkage among groups of authors that formed clusters while other authors remained disconnected. Among countries United States, China and the United Kingdom had a higher impact on publications and citations. Our analysis showed that there is still scope for collaboration among countries as there is no evidence of multidisciplinary interlinkages. By understanding the current research landscape, identifying influential works and authors, and uncovering collaboration patterns, we can pave the way for future advancements in potato seed production. Ultimately, this research contributes to achieving sustainable agriculture and ensuring food security for future generations.